A TRAILR2/CDH3 bispecific antibody demonstrates selective apoptosis and tumor regression in CDH3-positive pancreatic cancer - Peter Jung; Stefan P. Glaser; Jing Han; Alexandra Popa; Laura Pisarsky; Ningping Feng; Antonia Geyer; Franziska Haderk; Donat Alpar; Christopher Bristow; Susanne Schmittner; Paula-Elena Traexler; et al. (mAbs)
Exploitation of extrinsic apoptosis signaling via TRAILR2 activation represents a promising therapeutic concept in cancer treatment. The limited clinical success of previous TRAILR2 agonistic agents, to date, has been ascribed to either poor efficacy or hepatotoxicity. TR2/CDH3 BAB is a human bispecific antibody that relies on binding both CDH3 and TRAILR2 on cell surfaces to achieve TRAILR2 hyperclustering and efficient apoptosis induction by TRAILR2 signaling selectively in CDH3-expressing tumor cells. We demonstrate target-dependent TR2/CDH3 BAB anti-tumor activity in CRISPR/Cas9-engineered TRAILR2 or CDH3 knock-out cells. By utilizing the cell line screening platform PRISM, we found selective TR2/CDH3 BAB efficacy in various cancer types, such as pancreatic, gastric, colorectal, and triple negative breast cancer. The efficacy of TR2/CDH3 BAB correlated with caspase activation in cancer cell lines and in xenograft tumor tissues. In pancreatic ductal adenocarcinoma (PDAC), where patient benefit from current cytotoxic therapy options is unsatisfactory, a close to uniform cell surface expression of CDH3 and TRAILR2 was observed, which will qualify the majority of PDAC patients for TR2/CDH3 BAB-based treatment. TR2/CDH3 BAB demonstrated anti-tumor activity in a panel of PDAC patient-derived xenograft models, including tumor regressions. By combining TR2/CDH3 BAB with chemotherapeutic agents, deeper and more sustained anti-tumor responses were observed when compared to monotherapy. Together with the potential to deliver a favorable safety profile, these data support clinical testing of TR2/CDH3 BAB in patients with PDAC.